CD155 Promotes the Progression of Cervical Cancer Cells Through AKT/mTOR and NF-κB Pathways - Liu, Lu; Wang, Ying; Geng, Chen; Wang, Aihong; Han, Sai; You, Xuewu; Sun, Yu; Zhang, Junhua; Lu, Wei; Zhang, Youzhong (Frontiers in Oncology, 2021)
Expression of the immunoglobulin superfamily member CD155 was increased in a variety of human malignancies, but the role of CD155 in tumorigenesis and tumor development in cervical cancer has not been elucidated. In this study, immunohistochemistry and enzyme-linked immunosorbent assay analyses showed that CD155 expression gradually increases with the degree of cervical lesions. In vitro and in vivo, reducing the expression of CD155 inhibited cell proliferation, cell viability and tumor formation and arrested the cell cycle in G0/G1 phase. Antibody array-based profiling of protein phosphorylation revealed that CD155 knockdown can inhibited the AKT/mTOR/NF-κB pathway and activated autophagy and apoptosis; the opposite effects were observed upon CD155 has overexpression. We proved that there is an interaction between CD155 and AKT by immunoprecipitation. We further confirmed the mechanism between CD155 and AKT/mTOR/NF-κB through rescue experiments. AKT knockdown reversed the anti-apoptotic effects and activation of the AKT/mTOR/NF-κB pathway induced by CD155 overexpression. Our research demonstrated that CD155 can interact with AKT to form a complex, activates the AKT/mTOR/NF-κB pathway and inhibit autophagy and apoptosis. Thus, CD155 is a potential screening and therapeutic biomarker for cervical cancer.